Analisis Formulasi Kue Kering Tinggi Protein sebagai Intervensi Gizi untuk Balita Stunting di Kota Tangerang - Maharani Kusuma Dewi; Meilita Dwi Paundrianagari; Zakiyah Mujahidah (Nindikayla Institute, 2024)
Stunting in toddlers is a chronic nutritional problem that requires comprehensive intervention. This study aims to analyze the formulation of high-protein cookies as a nutritional intervention for stunted toddlers in Tangerang City. This case study uses a descriptive approach by examining the composition of raw materials, the formulation process, physicochemical characteristics, and potential as a nutritional intervention. Data were obtained from document analysis, interviews with nutritionists and producers, and a literature review. The analysis results indicate that the high-protein cookie formulation has the potential to be an effective supplementary food, but requires attention to consumer acceptance and food safety. Key findings include the identification of optimal protein sources, nutrient proportions appropriate to the needs of stunted toddlers, and an evaluation of the potential positive impact on nutritional status. The study concludes that high-protein cookies have the potential to be an innovative solution in efforts to reduce stunting in Tangerang City, with the need for formulation improvements and further testing. Recommendations include sustainable product development, increased nutrition education, and policy support from the local government.